2018
DOI: 10.1002/pon.4880
|View full text |Cite
|
Sign up to set email alerts
|

Towards the validation of a new, blended theoretical model of fear of cancer recurrence

Abstract: These results provide support for a blended FCR model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 35 publications
10
72
1
2
Order By: Relevance
“…It should be noted that many new models raised after Lee‐Jones et al's work. For instance, Lebel et al tested a blended model of FCR that integrates Leventhal's Common Sense Model, Mishel's Uncertainty in Illness Theory, and cognitive theories of worry. They found that integrated factors (eg, triggers, belief system, and intolerance of uncertainty) all played a critical role in the maintain of FCR.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that many new models raised after Lee‐Jones et al's work. For instance, Lebel et al tested a blended model of FCR that integrates Leventhal's Common Sense Model, Mishel's Uncertainty in Illness Theory, and cognitive theories of worry. They found that integrated factors (eg, triggers, belief system, and intolerance of uncertainty) all played a critical role in the maintain of FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we may ask “what coping strategies ameliorate fear of recurrence?” Patients with high intolerance of uncertainty and positive metacognitive beliefs about worry seem at a higher risk to engage in maladaptive behavioral processes such as avoidance, checking behaviors, and seeking constant reassurance from physicians . However, patients do not adopt the same coping responses, exemplified by Galica et al who found that the dimensions of the Fear of Cancer Recurrence Inventory (FCRI) did not load on a single second‐order factor, indicating that the subscales, including coping strategies, should not be combined into a total fear of cancer recurrence score.…”
Section: Who Is At Risk For and What Helps Existential Distress?mentioning
confidence: 99%
“…Psychological distress covers a wide spectrum ranging from normal feelings of vulnerability to problems that can become disabling, such as depression, anxiety, or extensive worries 7 . Results from previous studies in cancer patients showed that fear of cancer recurrence (FCR), defined as fear, worry, or concern about cancer returning or progressing, has been identified as one of the most common psychological challenges 8,9 . Studies on cancer worry in screening populations are limited and primarily conducted in screening populations with increased cancer risk 10,11 .…”
Section: Introductionmentioning
confidence: 99%